LOVE IN THE QUR’AN: EXPLORING MULTIFACETED DIMENSIONS THROUGH THE ANALYTICAL LENS OF MAKĀRIM SHĪRĀZĪ’S TAFSĪR AL-AMTHAL - Maria Ulfah, Lu'lu'atul; Baihaki, Egi Sukma; Gama, Cipta Bakti; Fadel, Achmad (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2024)
The study of love in the Qur’an has predominantly focused on its psychological dimension, viewing it as a manifestation of human emotions. However, the Qur’an places love in a broader context, emphasizing the centrality of God and transcending conventional subject-object relationships. Notably, the verses addressing love in the Qur’an often overlook its multifaceted dimensions. The contemporary discourse on reinterpreting religion through the lens of love underscores the need to comprehend the implications of love’s interpretation in exegesis books. Grounded in this context, this research aims to unravel the dimensions and implications of love’s meaning in Makārim Shīrāzī’s exegesis, al-Amthal. Employing an interpretative approach, the findings reveal four dimensions proposed by Makārim Shīrāzī: firstly, a philosophical dimension rooted in the dichotomy of genuine and illusory love; secondly, a religious dimension positioning love as the “substance of religion”; thirdly, a social dimension where love forms the basis for tranquility (iṭmi‘nān) and societal peace (sakan); and finally, a psychological dimension portraying love as an emotion existing alongside hatred. These dimensions bear implications for issues related to divinity, prophethood, social relations, and tolerance. This research contributes to refining the interpretation of love in Islam, fostering a nuanced understanding that transcends exclusive and extreme religious perspectives.